How did lockdown and social distancing policies change the eating habits of diabetic patients during the COVID-19 pandemic? A systematic review - Lashkarbolouk, Narges; Mazandarani, Mahdi; Pourghazi, Farzad; Eslami, Maysa; Khonsari, Nami Mohammadian; Ghonbalani, Zahra Nouri; Ejtahed, Hanieh-Sadat; Qorbani, Mostafa (Frontiers in Psychology, 2022)
Background: After the declaration of the COVID-19 pandemic, governments established national lockdowns and social distancing as an effective plan to control this disease. As a result of the lockdown policies, diabetic patients` access to food products, medication, and routine follow-ups is disrupted, making it difficult for them to control their disease. Methods: International databases, including PubMed/Medline, Web of Science, and Scopus, were searched until April 2022. All observational studies included assessing the impact of lockdown and social distancing on eating habits (as primary outcome) and glycemic and anthropometric indices (as secondary outcomes) of diabetic patients during the COVID-19 pandemic. The Newcastle-Ottawa Quality Scale was used to assess the quality rating of the studies. Results: Overall, 22 studies were included in this systematic review, the results of which varied in different communities. In most studies, consumption of grains, fruits, and vegetables was reported to increase. On the other hand, consumption of snacks and sweets was reported to increase in other surveys. During the COVID-19 lockdown, most diabetic patients preferred to cook meals at home, using less takeout, fast foods, and alcoholic drinks. Although the patients mostly improved their eating habits, the glycemic and anthropometric indices were contradictory in different studies. Studies showed that the eating habits of diabetic patients vary from country to country, even in some cases and studies done in the same country showed different results. For example, all the studies done in Japan showed an increase in the consumption of snacks and sweets, leading to weight gain in the patients. However, conflicting results in eating habits have been observed in studies conducted in India. Conclusion: The lockdown policies have led to a beneficial change in the eating habits of diabetic patients to consume more fruits and vegetables and reduce the consumption of animal protein products and alcoholic beverages. While some diabetic patients have increased consumption of snacks and sweets, leading to a disturbance in their glycemic and anthropometric indices control. Understanding the consequences of lockdown and social distancing of the diabetic patient during the covid-19 pandemic can help public health authorities make better recommendations to improve glycemic control.